2021
DOI: 10.1016/j.jhep.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 massive testing: A window of opportunity to catch up with HCV elimination

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We read with interest the paper by Crespo et al , who suggested that mass severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) testing offers a unique opportunity to screen for viral hepatitis, particularly hepatitis C virus (HCV) infection [ 1 ].…”
mentioning
confidence: 99%
“…We read with interest the paper by Crespo et al , who suggested that mass severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) testing offers a unique opportunity to screen for viral hepatitis, particularly hepatitis C virus (HCV) infection [ 1 ].…”
mentioning
confidence: 99%
“…We read with interest the article by Blach S et al to do so(4). We believe that that time is now and we must and can combat the J o u r n a l P r e -p r o o f dual threats of SARS-CoV-2 and HCV infection jointly, as has recently been suggested (6).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%
“…It has been proposed to incorporate different diagnostic options into care circuits during the pandemic, along with measures to prevent the spread of COVID-19 (19). In this regard, HCV screening has been promoted in conjunction with COVID-19 diagnostic tests or with routine vaccination (20), such as the experience published in Italy by Giacomelli A. et al, in patients over 50 years of age with a participation rate close to 50% (21); or even considering a more simplified circuit using the DBS for joint screening (22). Additionally, given the least impact achieved at the hospital as opposed to the primary level during the pandemic, promoting diagnosis at the primary care level should be considered (23,24).…”
Section: Discussionmentioning
confidence: 99%